The Impact of Self Efficacy to the Entrepreneurship Motivation in Generation Y - Octa Nilam Lukkita Aga; Eva Fauziana (Jurnal Ekonomi, 2022)
This research finds the core relationship between self-efficacy and entrepreneur motivation in generation Y. The limit of the study was the number of respondents and also the domicile where they were located, were limited in West Java areas. The research using mixed methods, between qualitative and quantitative methods. The authors spread questionnaires to 141 respondents ages 19-45 in order to get their perspectives on their motivation to build their own enterprises, compared with their self-efficacy. The results found out that mostly their motivation mostly in moderate levels. Their preferences to have stable career rather than building own business, caused by many factors explained detail below.